Investigating the Physical Activity Behaviour and Exercise Capacity of Pediatric Cardiomyopathy Patients - Moncion, Kevin (Université d'Ottawa / University of Ottawa, 2018)
Background: Physically active lifestyles are important for health and quality of life across all stages of development. Exercise interventions have recently been incorporated as an effective strategy for adult cardiomyopathy patients, but have yet to be examined in children with cardiomyopathy. The overall goal of this pilot study was to provide preliminary data on whether there is a need to develop exercise interventions among children with cardiomyopathy. This study sought to characterize the moderate-to-vigorous physical activity (MVPA) level, submaximal exercise capacity and physical activity barriers among children with cardiomyopathy. Methods: This study employed a mixed-methods approach. Children were eligible if they were between the ages of 5 to 17 years, had a medical diagnosis of cardiomyopathy (i.e. hypertrophic, dilated, or cancer induced), atrial septal defect, or had been identified as carrying a genetic risk for cardiomyopathy. Participants were excluded if they had physical activity contraindications, had a non-cardiac medical condition or disability known to influence physical activity, or if they underwent cardiac surgery within the preceding 6 months. MVPA was assessed using 7-day omnidirectional accelerometry. Submaximal exercise capacity was determined by intermittent treadmill protocol targeting 40% to 80% of predicted maximum heart rate. Physical activity barriers were identified through semi-structured interviews, which were audio-recorded and transcribed verbatim for thematic analysis using Braun & Clark’s approach. Results: Pediatric cardiomyopathy patients (n=5) were compared to children who are genotypepositive but phenotype-negative for cardiomyopathy (n=5), children with simple congenital heart defects (CHD, n=8) and published data for Canadian children (n=1,300). Daily MVPA (48.2 ± 19.0 minutes) was variable but did not differ significantly between groups (η2=0.025, p=0.82) or from published data on Canadian children (t(17) = -1.52 p=0.15). Submaximal exercise testing revealed that children with cardiomyopathy may be able to participate in activities at moderate intensities (i.e. 4.5 ± 3.1 METs) at 150 beats per minute (bpm). Children with cardiomyopathy reported primarily disease-centred barriers to participation, including physical activity restriction and physical influences from the disease which were not reported by children who carry a genetic risk for cardiomyopathy. Conclusion: These novel data within this population group suggest that pediatric cardiomyopathy patients may have sufficient submaximal exercise capacity to participate in moderate physical activity, despite reporting disease centered barriers to physical activity. A diagnosis of cardiomyopathy may not preclude these children from achieving and healthy, active lifestyle, but their current level of participation is less than recommended for optimal health and cardiac function.
Keywords: Physical activity; Pediatric Cardiomyopathy; Exercise Physiology; Barriers; Health Behaviours